#TITLE_ALTERNATIVE# - MILZA KHALIDA (NIM 12206030); Pembimbing: Ir. Pudjo Sukarno, M.Sc., Ph.D., RISKA
In this research, simulation and performance analysis of an oil field that has four wells done with gas lift method. Injection gas requirements each well known by Gas Lift Performance Curve (GLPC). To obtain the maximum production, each well should be injected with optimum injection rate of gas everyday. But sometimes, there are not enough gas for optimum requirement. Therefore it is necessary to allocate the available gas injection with allocation gas injection method using equal slope to increase the recovery. Reservoir simulation in this final assignment is integrated modeling system that include reservoir system, production and surface facilities system. The heterogeneous reservoir model was built with Petrel and produced through ECLIPSE. The production and surface facilities model was made and simulated using PIPESIM. Both models are combined using Field Planning Tool (FPT). The purpose of this final assignment is to determine the optimum production and improve recovery with gas allocation and integrated system.